Transformasi Digital bagi UMKM di Desa Ngusikan: Sosialisasi dan Pendampingan Penggunaan Digital Marketing - Muhammad Husen; Imam Bayhaki; Septian Ragil Anandita; Wisnu Mahendri; Akhmad Taqiyuddin; M. Nur Zhaki; Muhammad Ibrahim; Muhammad Andi; Ayu Musthofiyah; Nila Dianingsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
This community service project was aimed at increasing the sales turnover of MSMEs (Micro, Small, and Medium Enterprises) in Ngusikan Village through digital marketing and administrative assistance. The project involved training and hands-on assistance in optimizing social media usage, improving branding, and completing business administration such as obtaining business licenses (NIB) and halal certification. The approach taken was a combination of workshops and field assistance with the MSMEs. The results indicate a significant improvement in the knowledge and practices of MSME actors in digital marketing, leading to a substantial increase in sales turnover and market visibility.